The applications of social commerce constructs - Shanmugam, Mohana; Sun, Shiwei; Amidi, Asra; Khani, Farzad; Khani, Fariborz (Elsevier, 2016)
Social commerce has evolved quickly in practice and gained attention in the IS discipline. However, trust has remained a vital component and is dominantly worth investigating. The purpose of this study, therefore, is to examine the roles of social commerce constructs and social support constructs (i.e., emotional support and informational support) in establishing trust on online community platforms. The study will apply the theoretical foundation of social commerce constructs proposed by Hajli. In order to provide a detailed understanding of the proposed model, a quantitative study involving a survey data gathered from online communities in Malaysia, including Facebook, Trip Advisor and LinkedIn was conducted. The data was analyzed and hypotheses were tested with structural equation modeling (SEM). Our results shed some lights on social commerce literature. The findings show that there are significant effect of social commerce constructs on social support, namely the emotional and informational support, and in turn, on trust- building.